Diferenciais de gênero no letramento financeiro de candidatos ao Exame Nacional do Ensino Médio - Charles Henrique Correa (2012)
Financial literacy is a key factor for financial decision-making. Especially, young people seem to enter the labor market with the challenge of taking increasingly important financial responsibilities, including accumulation of savings for retirement. On the other hand, we realize that financial literacy of men and women seem to differ in the literature. Although women generally have a lower financial literacy vis-à-vis men, they have characteristics that require a more appropriate financial literacy. On average, women earn less and have a more conservative investment profile, as well as live longer and retire earlier. In this study, we evaluated the financial literacy of candidates (mostly young) to the National High School Exam (ENEM) 2005 with a focus on gender differences. We sought to evaluate the performance of men and women on two financial questions of the exam, controlling for demographic and socioeconomic factors. The results indicate a low financial literacy for both sexes and better performance of men in both cases. Even in the presence of control variables, gender difference still remained statistically significant, although it has declined.